Spring 6 recipes : a problem-solution approach to Spring framework - Deinum, Marten; Rubio, Daniel; Long, Josh (Apress, 2023)
This in-depth Spring-based Java developer code reference has been updated and now solves many of your Spring Framework 6 problems using reusable, complete and real-world working code examples. Spring 6 Recipes (5th Edition) now includes Spring Native which speeds up your Java-based Spring Framework built enterprise, native cloud, web applications and microservices. It also has been updated to now include Spring R2DBC for Reactive Relational Database Connectivity, a specification to integrate SQL databases, like PostgreSQL, MySQL and more, using reactive drivers. Furthermore, this book includes additional coverage of WebFlux for more reactive Spring web applications. Reactive programming allows you to build systems that are resilient to high load, especially common in the more complex enterprise, native cloud applications that Spring Framework lets you build. This updated edition also uses code snippets and examples based on newest available standard long term support release of Java. When you start a new project, you'll be able to copy the code and configuration files from this book, and then modify them for your specific Spring Framework-based application needs. This can save you a great deal of work over creating a project from scratch. This powerful code reference is a "must have" for your print or digital library. This developer cookbook comes with accompanying source code that is freely available on GitHub under latest Creative Commons open source licensing.